Assessment of Information Literacy Competencies of Practicing Nurses at Kenyatta National Hospital, Kenya - Mugambi, Frankline M. (Kenyatta University, 2017)
The aim of the research project was to assess the information literacy competency skills of practicing nurses at KNH with the objective of establishing, the information needs of practicing nurses, awareness of potential sources of information in nursing profession, ability to evaluate the retrieved information and establish their knowledge of ethical, legal and social-economic issues surrounding information use. The research adopted a case study focusing on single case of KNH, with a target population of 1723 registered nurses and a sample size of 347 respondents was selected. Structured questionnaires were used to collect data. Data was analyzed by use of likert scale and SPSS and presented through tables, charts, figure, graphs and percentage. The study established that information literacy program is taught at nursing schools in Kenya, four professional information needs were cited by practicing nurses at KNH; patient care, in-house presentation, presentation at a professional meeting/seminar and scholarship application/career development. Patient care recorded the highest frequency of 163(83%). All practicing nurses at KNH were aware of reference books, textbooks and human sources as sources of professional information. Human source was most preferred source of information; only 41% of practicing nurses had access to online medical databases since graduating. Low information literacy skills was reported on evaluation of information retrieved, use of online medical databases and on intellectual properties. The research recommends establishment of conducive environment for sharing professional knowledge, establishment of an information center to acquire information resources and develop specialized information services as well as information literacy programme tailor made to nurses and other medical practitioners in support of evidence based practice. The insights from the research findings will help nursing schools across the country in designing of information literacy curriculum, help health organizations in design of information literacy policies and staff trainings, guide future researchers and contribute to the professional knowledge
Keywords: Information Literacy; Nurses; Kenya